Pengembangan Media Scrapbook untuk Meningkatkan Kemampuan Menyelesaikan Soal Cerita FPB Dan Kpk Kelas IV SD - Fitriyah, Lailatul; Suryatin, Suryatin; Tisngati, Urip (PGSD STKIP PGRI Pacitan, 2022)
This study is based on the potential and requirements of mathematics learning media in elementary schools for supporting the learning process. The research is purposed to produce a learning media such as Scrapbook to Improve Grade IV Elementary School Students' Ability to Solve Highest Common Factor (HCF) and Lowest Common Multiple (LCM) Story Problems. This research was a kind of Research and Development (R&D) which the procedure used a Borg & Gall development model that is limited to the seventh step. The subject of the research was 7 students of the 4th grade at SDN 1 Karanggede. Techniques for collecting data include questionnaires, written tests, and documentation. The study's findings are as follows: (1) Media Scrapbook was created using Borg and Gall development procedures to the seventh step; (2) Scrapbook media was declared